﻿The new S2k Guideline: Medical compression therapy of the extremities with medical compression stockings (MCS), phlebological compression bandages (PCB) and medically adaptive compression systems (MCS) - Stücker, Markus; Rabe, Eberhard (Phlebologie, 2019)
For the first time, the new guideline for medical compression therapy addresses the different options of phlebological compression therapy. It assigns the phlebological compression bandage (PCB) and the medically adaptive compression system (MAC) primarily to the decongestion phase, medical compression stocking (MCS) to the maintenance phase. The use of flat-knit MCS is not attributed to a specific diagnosis, but to specific findings of the patient. The higher stiffness allows the use with therapy-resistant edema, the higher flexural rigidity in case of skin folds and the ability to individually increase or decrease the stitches of flat knitwear the use of exceptional caliber differences of the legs. In order to improve adherence, the lowest possible compression classes should be used for MCS. Many aspects of PCB have to be taken into account, from which results the limitation of PCB to the decongestion in this guideline. More than ever before, the goal of compression therapy is to improve patient’s quality of life.
Keywords: Compression; flat knitwear; circular knitwear; decongestion phase; maintenance phase